Isolation of Bacterial Species Capable of Producing Polyhydroxyalkanoate - & Nwinyi Obinna C., Akinmulewo Adebola B. (Covenant Journal of Physical and Life Sciences, 2019)
The major threat posed by petroleum-based plastics is environmental pollution, which further leads to death of marine animals from the plastic toxicity. A continuous scientific research on plastic innovations would help solve the plastic menace. Hence, this study was carried out to isolate and characterize microbial strains from high organic deposit sites capable of polyhydroxyalkanoate (PHA) production. Samples of soil and organic wastes were collected from Olusosun dumpsite, Ojota, motor mechanic shop at Covenant University, Ota and kitchen sewage from Covenant University’s Cafeteria 2. Twenty bacterial isolates were obtained and screened for the ability to utilize waste frying oil and cassava effluent as cheap carbon substrates to synthesize PHA polymers. Quantitative analysis was carried out after 72 hours by crotonic assay method using the UV spectrophotometer at 235 nm wavelength. The result showed that there is no significant difference (p<0.05) between the PHA accumulated when either substrates are utilized by the isolates. The quantitative analysis result for the identification of monomeric units of PHA using Gas chromatography-mass spectrometry showed four isolates with capacities to yield more PHAs than other isolates under the subjected growth condition. These four isolates selected were characterized, morphological and phylogenetic characterization results showed that all four isolates A1 (MK989593), A2 (MK989594), A4 (MK989595), A6 (MK989596) have similarity (>90%) to the Alcaligenes spp. respectively. The use of waste oils and cassava effluent to produce PHAs by isolates used in this study can be considered good candidates for cheap substrates choices to further optimize PHA production industrially.